Impact of Mouthwash-Induced Oral Microbiome Disruption on Alzheimer's Disease Risk: A Perspective Review - Ayoub Boulares; Hela Jdidi; Nicola Luigi Bragazzi (International Dental Journal)
The widespread use of mouthwashes, particularly those containing chlorhexidine (CHX), has raised concerns about their impact on the oral microbiome and potential systemic health effects. This perspective review examines the current evidence linking CHX mouthwash use to disruptions in the oral microbiome and explores the potential indirect implications for Alzheimer's disease (AD) risk. CHX mouthwash is effective in reducing dental plaque and gingival inflammation, but it also significantly alters the composition of the oral microbiome, decreasing the abundance of nitrate-reducing bacteria critical for nitric oxide (NO) production. This disruption can lead to increased blood pressure, a major risk factor for AD. Given the established connection between hypertension and AD, the long-term use of CHX mouthwash may indirectly contribute to the onset of AD. However, the relationship between CHX mouthwash use and AD remains largely indirect, necessitating further longitudinal and cohort studies to investigate whether a direct causal link exists. The review aims to highlight the importance of maintaining a balanced oral microbiome for both oral and systemic health and calls for more research into safer oral hygiene practices and their potential impacts on neurodegenerative disease risk.